Use Information Sharing Environment Concept To Design Electronic Intelligence Framework For Support E-Government : Iraq As Case Study - Abaas, Thamer; Shibghatullah, Abdul Samad; Musa Jaber, Mustafa (Scientific & Academic Publishing, 2014)
-